Students' perspective on inclusion: Relations of attitudes towards inclusive education and self-perceptions of peer relations. (2020) - Spörer, Nadine; Lenkeit, Jenny; Bosse, Stefanie; Hartmann, Anne; Ehlert, Antje; Knigge, Michel
Highlights: Students' attitudes and classroom climate were longitudinally assessed. Students' diagnosed SEN and self-perceived difficulties were recorded. Self-perceived difficulties were negatively related to classroom climate. Students' attitudes positively predicted changes in classroom climate. Abstract: The goal of the present study was to analyze how students' attitudes towards inclusive education develop over the course of a school year and how these attitudes relate to students' peer relations. Sixth- and seventh-graders of 44 inclusive classes filled out a questionnaire at two measurement points within one school year to assess attitudes towards inclusive education and peer relations. Applying multilevel regression analyses it turned out that changes in peer relations over time were positively predicted by students' attitudes towards instructional adaptations for students with behaviour difficulties. Further, students with self-perceived behavior difficulties reported lower scores for peer relations compared to students without self-perceived difficulties. Results are discussed with respect to structural factors and individual characteristics affecting inclusive education.